2012
DOI: 10.2298/bah1201025p
|View full text |Cite
|
Sign up to set email alerts
|

Use of metabolic profiles and body condition scoring for the assessment of energy status of dairy cows

Abstract: The aim of this study was to assess the significance of body condition scoring and metabolic profile test for estimation of energy status of healthy high-yielding dairy cows. Twenty one healthy cows (primiparous and secundiparous) were divided into three groups: dry cows, early puerperal cows and early lactating cows. Cow's energy status was estimated by the analysis of blood samples for beta-hydroxybutirate (BHBA) and glucose. Additionally, urea, total bilirubine and total protein were measured in blood serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Moss and Murray 92 found higher plasma urea concentration due to supplementary protein intake in dairy calves. A significant positive correlation between urea nitrogen and the content of lipid in the liver 10 days after calving has been reported by Prodanović et al 87 Roche et al 93 found that high-protein diets fed to postpartum cows lead to increased blood urea and lower fertility.…”
Section: Protein Statusmentioning
confidence: 68%
See 4 more Smart Citations
“…Moss and Murray 92 found higher plasma urea concentration due to supplementary protein intake in dairy calves. A significant positive correlation between urea nitrogen and the content of lipid in the liver 10 days after calving has been reported by Prodanović et al 87 Roche et al 93 found that high-protein diets fed to postpartum cows lead to increased blood urea and lower fertility.…”
Section: Protein Statusmentioning
confidence: 68%
“…Blood serum bilirubin is elevated in early lactation owing to its diminished hepatic uptake in favor of NEFA uptake . Prodanović et al . reported that total bilirubin concentration increased significantly from the dry (6.31 ± 0.37 mmol L −1 ) to the puerperal (7.63 ± 2.52 mmol L −1 ) period.…”
Section: Protein Statusmentioning
confidence: 99%
See 3 more Smart Citations